2014
DOI: 10.3386/w19805
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Migrants: A Field Experiment on Financial Decision-Making in Transnational Households

Abstract: We randomly assigned male migrant workers in Qatar invitations to a motivational workshop aimed at improving financial habits and encouraging joint decision-making with spouses back home in India. 13-17 months later, we surveyed migrants and wives to estimate intent-to-treat impacts in their transnational households. Wives of treated migrants changed their financial practices, and became more likely to seek out financial education themselves. Treated migrants and their wives became more likely to make joint de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…Cole et al (2011) found no significant average impact of financial literacy training on the likelihood of households opening a bank account in Indonesia, while Gibson et al (2014) find that financial literacy training for migrants in the destination country lead to changes in financial knowledge, but no change in remitting behaviors. Seshan and Yang (2014) obtain results someway between those studies and ours, with no significant effects on savings and remittances in the full sample, but some impacts in a sub-sample of individuals with low baseline savings. Our results therefore raise the question of why effects are stronger in our context, and why they vary by treatment status.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Cole et al (2011) found no significant average impact of financial literacy training on the likelihood of households opening a bank account in Indonesia, while Gibson et al (2014) find that financial literacy training for migrants in the destination country lead to changes in financial knowledge, but no change in remitting behaviors. Seshan and Yang (2014) obtain results someway between those studies and ours, with no significant effects on savings and remittances in the full sample, but some impacts in a sub-sample of individuals with low baseline savings. Our results therefore raise the question of why effects are stronger in our context, and why they vary by treatment status.…”
Section: Discussionsupporting
confidence: 55%
“…As such, the remaining family members may have less experience and skill at financial decision-making, and so training can especially help. This contrasts from other migration studies where the migrant is male, and his spouse is the one left behind, as in Seshan and Yang (2014). Examining impacts in other contexts with different types of migrants is an interesting area for future research, as is using larger samples to provide more precision in testing for these complementarities.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The conducted pilot study has shown that the Poles living in the UK more often waste food as compared to the Pole living in Poland. This can be a signal that the radical change of the residence place and the hazards related to its cause that immigrants cope less skillfully with the management of their budget and planning of their daily expenses, which also confirms in their research (Seshan and Yang, 2014). Poland more and more often becomes the place of residence for immigrants, especially from the East.…”
Section: Discussionmentioning
confidence: 69%